Mechanisms of Cryoprotectant Permeation via Erythrocytes Membranes - Gordienko, O. I.; Gordienko, E. A.; Linnik, T. P.; Kompaniets, A. M. (Problems of Cryobiology and Cryomedicine, 2002)
The experimental data on permeability coefficients of human erythrocyte membranes for the series of cryoprotectants are presented. It is shown, that permeability coefficients are affected by both geometrical and physical and chemical parameters of molecules. The obtained results propose that when exceeding the molecules’ diameter over the value of 4D, the permeability coefficient reduces, perhaps, due to the decreasing of flow through the aqueous protein pores of a constant size. Permeability coefficients for comparatively hydrophobic molecules are almost directly proportional to the coefficients of partition between hydrophobic and hydrophilic phases, by pointing to a lipid way of permeation of these molecules through erythrocyte membranes.